Implementasi Kebijakan Perjalanan Orang Dalam Negeri Dengan Transportasi Udara Pada Masa Pandemi Covid-19 di Bandar Udara Sultan Bantilan Tolitoli - Muhammad Iqbal (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the implementation of domestic travel policies by air transportation during the COVID-19 pandemic in breaking its spread at airport of Sultan Bantilan Tolitoli. This type of research is descriptive with a qualitative approach. 6 informants were selected by purposive sampling. Collecting data is through observation, interview and documentation. Furthermore, the stages of data reduction, data presentation, conclusion and verification. Results of the study were analyzed by model of successful policy implementation according to Merilee S. Grindle. Results of the study, the airport of Sultan Bantilan Tolitoli has clearly understood the travel rules by air transportation. However, there was still not enough socialization to prospective passengers. The determination of the high administration fee for rapid antigen and the refusal of vaccination by prospective passengers